Relevar y reconocer nuestro territorio: el mapeo colectivo como estrategia de resistencia: To Survey and Recognize Our Territory: Collective Mappingas a Resistance Strategy - Coronel, Silvia; Garay, Ana; Ledesma, Dominga; Maguna, Macarena (Revista Geográfica de América Central., 2025)
of accumulation in the 1990s and becoming consolidated at the beginning of the 21st century. In this context, the emerging conflicts gave rise to spaces for the organization of local communities throughout the province. In 2009, the Mesa de Tierras del Dpto. Jiménez emerged from the confluence of peasant, governmental and non-governmental organizations, local communities and the Catholic Church. The objective of this article is to analyze the collective mapping process carried out between 2021 and 2022. The methodology used is qualitative, based on the following techniques: data recording and analysis, participant observation and semi-structured interviews.